Diasporic Identity in Bharati Gautam’s Memoirs - Timalsina, R. (The Journal of Knowledge and Innovation, 2022)
This article aims to explore how Bharati Gautam’s collection of memoirs Vigata ra Baduli [Past and Hiccups] exhibits the formation of a diasporic self. The text connects the Nepali American writer with both of her homeland (Nepal) and hostland (the USA). Dean Smyer Yu’s theorization of diasporic selfhood and identity guides the analysis. Yu argues that the people who consciously choose to make their new home in the diaspora work for their self-making and place making that ultimately manifests their transnational and trans local mode of being. Their identity develops as a hybrid one because of the admixture of the culture, emotion, thought pattern and practicality from both the lands. Gautam’s memoirs present the same tendency of her growth in the America for about four decades. Her identity is constantly in the making and so she goes on modifying her life and thoughts to adapt in the new land. She gradually develops a diasporic consciousness that helps her accept the differences between the homeland and hostland life as a transnational individual. Finally, her family evolves a cosmopolitan consciousness. This article will contribute to the study of the making of the diasporic self the Nepali people have been undergoing for long.